2020
DOI: 10.3390/cancers12113240
|View full text |Cite
|
Sign up to set email alerts
|

The Contribution of MicroRNAs to the Inflammatory and Neoplastic Characteristics of Erdheim–Chester Disease

Abstract: The pathogenesis of histiocytic neoplasms is driven by mutations activating the MAPK/ERK pathway, but little is known about the transcriptional and post-transcriptional alterations involved in these neoplasms. We analyzed microRNA (miRNA) expression in plasma samples and tissue biopsies of Erdheim–Chester disease (ECD) and Langerhans cell histiocytosis (LCH) patients. In silico analysis revealed a potential role of miRNAs in regulating gene expression in these neoplasms as compared with healthy controls (HC). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 90 publications
0
2
0
Order By: Relevance
“… 13 We recently demonstrated that the PI3K-AKT-mTOR pathway is upregulated in patients with histiocytosis via alterations in microRNAs (miRNAs/miRs) governing PI3K/mTOR activation. 14 Moreover, we previously identified somatic hotspot activating mutations in PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha), which encodes the p110α protein, the catalytic subunit of PI3K, in several patients with ECD ( Figure 1 A-B). 6 , 15 These mutations have been demonstrated to increase the kinase activity of PIK3CA and contribute to cellular transformation in solid tumor models with concomitant phosphorylation of proteins in the AKT pathway.…”
Section: Introductionmentioning
confidence: 98%
“… 13 We recently demonstrated that the PI3K-AKT-mTOR pathway is upregulated in patients with histiocytosis via alterations in microRNAs (miRNAs/miRs) governing PI3K/mTOR activation. 14 Moreover, we previously identified somatic hotspot activating mutations in PIK3CA (phosphatidylinositol-4,5-bisphosphate 3-kinase catalytic subunit alpha), which encodes the p110α protein, the catalytic subunit of PI3K, in several patients with ECD ( Figure 1 A-B). 6 , 15 These mutations have been demonstrated to increase the kinase activity of PIK3CA and contribute to cellular transformation in solid tumor models with concomitant phosphorylation of proteins in the AKT pathway.…”
Section: Introductionmentioning
confidence: 98%
“…More than 50% of patients are positive for a BRAF mutation. BRAF V600 wild-type ECD lesions have been found to contain somatic mutations in the MAPK/ERK signaling pathway ( 9 ). In these cases, BRAF inhibitor therapy (vemurafenib, dabrafenib) is available under a compassionate use program.…”
Section: Introductionmentioning
confidence: 99%